An Agent-based Negotiation Model Selector for Managing Negotiation Processes in Corrective and Preventive Actions: A Conceptual Framework - Jaafar, Nur Huda; Ahmad, Mohd Sharifuddin (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Negotiation is an important process of management in any organizations especially if it involves quality management such as in corrective and preventive actions (CPA). The ability of software agent to implement automated negotiation can help organizations resolve or avoid conflicts. While many negotiation models have been developed, studies in intelligent selection of integrated negotiation models are still lacking. This paper proposes a conceptual framework for an agent-based negotiation model selector engine to resolve conflicts in the CPA activities. Several software agents will be involved to operate the proposed engine, in order to assist organizations in resolving conflicts and maintaining high quality management.